Anterior Glenohumeral Instability: Systematic Review of Outcomes Assessment Used in Brazil - Jorge Henrique Assunção; Eduardo Angeli Malavolta; Fernando José de Souza; Mauro Emilio Conforto Gracitelli; Arnaldo Amado Ferreira Neto (Revista Brasileira de Ortopedia, 2019)
Abstract A review involving the six major international orthopedic journals has been published recently. It described the tools used for the evaluation of outcomes in the surgical treatment of recurrent anterior dislocation of the shoulder. There are no studies that exhibit the main outcome tools for this disease in Brazil. The authors evaluated the outcomes of clinical studies involving anterior glenohumeral instability that were published in the last decade in the two leading Brazilian orthopedic journals, Revista Brasileira de Ortopedia and Acta Ortopédica Brasileira. A review of the literature was performed, including all clinical papers published between 2007 and 2016 describing at least one outcome measure before and after surgical intervention. The outcomes were range of motion, muscle strength, physical examination testing, patient satisfaction, return to sports, imaging, complications, and functional outcomes scores. Twelve studies evaluating the clinical outcomes of surgical treatment for anterior shoulder instability were published. Ten studies (83%) were case series (level of evidence IV), 1 (8%) was a case-control study (III), and 1 was a retrospective cohort (III). On average, the number of outcomes assessed was 3.7 ± 1.7. The Rowe score was used in 9 studies (75%), and 7 (58%) papers used the University of California Los Angeles (UCLA) scale. Ten studies (83%) reported complications related to surgical treatment. The complication most frequently reported was recurrent instability, found in 9 studies (75%). The national studies have preferentially used scales considered to be of low reliability, responsiveness, and internal consistency.